Activation of cross-reactive mucosal T and B cell responses in human nasopharynx-associated lymphoid tissue in vitro by Modified Vaccinia Ankara-vectored influenza vaccines. Issue 14 (29th March 2016) - Mullin, Jennifer; Ahmed, Muhammed S.; Sharma, Ravi; Upile, Navdeep; Beer, Helen; Achar, Priya; Puksuriwong, Suttida; Ferrara, Francesca; Temperton, Nigel; McNamara, Paul; Lambe, Teresa; Gilbert, Sarah C.; et al.
Highlights: MVA-vectored influenza vaccines are highly efficient in infecting human NALT. Tonsillar B cells are efficient in expressing the encoded vaccine antigen. MVA vaccine expressing highly conserved nucleoprotein (NP) elicits T cell response. MVA expressing pdmH1N1 HA can induce cross-reactive anti-HA antibodies. MVA vaccines may have the potential to be used as intranasal vaccines against influenza. Abstract: Recent efforts have been focused on the development of vaccines that could induce broad immunity against influenza virus, either through T cell responses to conserved internal antigens or B cell response to cross-reactive haemagglutinin (HA). We studied the capacity of Modified Vaccinia Ankara (MVA)-vectored influenza vaccines to induce cross-reactive immunity to influenza virus in human nasopharynx-associated lymphoid tissue (NALT) in vitro. Adenotonsillar cells were isolated and stimulated with MVA vaccines expressing either conserved nucleoprotein (NP) and matrix protein 1 (M1) (MVA-NP-M1) or pandemic H1N1 HA (MVA-pdmH1HA). The MVA vaccine uptake and expression, and T and B cell responses were analyzed. MVA-vectored vaccines were highly efficient infecting NALT and vaccine antigens were highly expressed by B cells. MVA-NP-M1 elicited T cell response with greater numbers of IFNγ-producing CD4+ T cells and tissue-resident memory T cells than controls. MVA-pdmH1HA induced cross-reactive anti-HA antibodies to a number of influenza subtypes, in an age-dependent manner. The cross-reactive antibodies include anti-avian H5N1 and mainly target HA2 domain. Conclusion : MVA vaccines are efficient in infecting NALT and the vaccine antigen is highly expressed by B cells. MVA vaccines expressing conserved influenza antigens induce cross-reactive T and B cell responses in human NALT in vitro, suggesting the potential as mucosal vaccines for broader immunity against influenza.